Pengaruh Kinerja Keuangan, Profitabilitas Dan Likuiditas Terhadap Harga Saham Dengan Kebijakan Deviden Sebagai Variabel Moderating Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020 - Indra Syafrin; Fasridon; Waldino Putra (Journal Of Science Education And Management Business, 2022)
Abstract. This study aims to determine the effect of financial performance, profitability and liquidity on stock prices with dividend policy as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sample in this study was taken using a purposive sampling technique with a total of 45 companies. The analytical technique used is panel data regression analysis with the help of the E-Views 10 program. The results of this study are that financial performance and liquidity have no effect on stock prices, while profitability has a significant positive effect on stock prices. Financial Performance and Liquidity have a positive and significant effect on Stock Prices through Dividend Policy, while Profitability has a negative and significant effect on Stock Prices through Dividend Policy.